Investigation of the influence of the type of charge on the characteristics of the shock tube - Loboda, Egor L. (Proceedings of SPIE)
The use of shock waves as a source of intense impact on the combustion process, in particular, on a wildfire or man-made fire, has been known in science for several decades. The discontinuity surface of hydrodynamic functions, which is the front of the shock wave, can stop combustion, or intensify the fire situation. An experimental setup with shock tube was made to study the effect of shock waves. This article presents the study results of the impact of the charge energy characteristics on the shock tube characteristics.